Avaliação do processo de implantação de auditoria interna governamental no DAAE de Araraquara - SP - Mattar, Gustavo Rodrigues (2022)
In the public sector Internal Control System (ICS), the internal audit function can assist in achieving organizational objectives and and in support of the External Control. The Governmental Internal Audit - AIG is the focal object of this research, whose results are now reported. GIA presents itself as an innovation in the Brazilian public sector after the publication of normative instructions nº 3 and 8 of the Brazilian Ministry of Transparency, Inspection and Comptroller-General of the Union – CGU, both from 2017, which approve the Technical Reference for GIA Activity of the Federal Executive Branch – FEB, and the Implementation Guide for the Professional Practice of GIA within the Brazilian FEB, becoming regulatory frameworks on GIA's role in public governance. This dissertation sought to adapt and create a methodology for the federal standards application in AIG activities of the SCI, exercised by the Department of Water Supply & Sanitation (DWSS) Controllership, municipal autarchy responsible for the basic sanitation of the city of Araraquara/SP. The action research, of qualitative nature, had the descriptive-exploratory double purpose, for describing the GIA implementing process, through two instruments: an operational procedure and a professional booklet, and for investigating, on an exploratory basis, the difficulties and advances observed, before and after, the implementation of a risk-based audit program in DWSS. Data collection was done through participant observation, in the GIA implementing process in the autarchy between 2018 and 2022. Aiming a data sources triangulating of the studied phenomenon, a documentary research was carried out on the sentences issued by the Sao Paulo State Court of Accounts (COA-SP) on the DWSS accounts between 2010 and 2020. Data analysis was performed using the content analysis technique of the external auditors written opinions, focusing on the excerpts that report the COA-SP findings, being both the qualifications (possible unqualifications) and the recommendations. As a result some categories of difficulties overcome and advances obtained after the GIA activity start, from 2018, were identified: increase in the resolution of COA-SP audit finding monitored and resolved by the autarchy; reduction in the number of COA-SP finding; ICS reporting improvements; greater use of ICS recommendations by COA-SP and autarchy´s management. The two technical products, which offer a practical model proposal for the GIA carrying out, points walkthrough instructions for the GIA tools use, from planning to the evaluation report issue. They can possibly be adapted and reproduced in other municipal sanitation bodies, in accordance with the CGU standards. They can possibly be adapted and reproduced in other municipal sanitation bodies, in accordance with the CGU standards. The research points to the progress into the relations between Internal Control and External Control, and the gradual strengthening of the DWSS-Araraquara accountability.